The slan antigen identifies the prototypical non-classical CD16+-monocytes in human blood - Tamassia, Nicola; Bianchetto-Aguilera, Francisco; Gasperini, Sara; Grimaldi, Alessio; Montaldo, Claudia; Calzetti, Federica; Gardiman, Elisa; Signoretto, Ilaria; Castellucci, Monica; Barnaba, Vincenzo; Tripodi, Marco; Cassatella, Marco Antonio (Frontiers in Immunology, 2023)
Peripheral monocytes in humans are conventionally divided into classical (CL, CD14++CD16−), intermediate (INT, CD14++CD16+) and non-classical (NC, CD14dim/−CD16++) cells, based on their expression levels of CD14 and CD16. A major fraction of the NC-monocytes has been shown to express the 6-sulfo LacNAc (slan) antigen, but whether these slan+/NC-monocytes represent the prototypical non-classical monocytes or whether they are simply a sub-fraction with identical features as the remainder of NC monocytes is still unclear. Therefore, we analysed transcriptome, proteome, cell surface markers and production of discrete cytokines by peripheral slan+/NC- and slan−/NC-monocytes, in comparison to total NC-, CL- and INT- monocytes. By bulk RNA-seq and proteomic analysis, we found that slan+/NC-monocytes express higher levels of genes and proteins specific of NC-monocytes than slan−/NC-monocytes do. Unsupervised clustering of scRNA-seq data generated one cluster of NC- and one of INT-monocytes, where all slan+/NC-monocytes were allocated to the NC-monocyte cluster, while slan−/NC-monocytes were found, in part (13.4 %), within the INT-monocyte cluster. In addition, total NC- and slan−/NC-monocytes, but not slan+/NC-monocytes, were found by both bulk RNA-seq and scRNA-seq to contain a small percentage of natural killer cells. Altogether, in addition to comparatively characterize total NC-, slan−/NC- and slan+/NC-monocyte transcriptomes and proteomes, our data prove that slan+/NC-, but not slan−/NC-, monocytes are more representative of prototypical NC-monocytes.